(untitled) (Al Dzahab, 2026)
Purpose: This study aims to examine the role of honesty-based accounting in preventing fraud in the management of School Operational Assistance (BOS) funds in vocational high schools. The study also explores supporting factors, including leadership integrity and organizational culture, that strengthen ethical financial governance in educational institutions. Design/Methodology/Approach: This research adopts a qualitative approach with a phenomenological design to understand the lived experiences of actors involved in BOS fund management. Data were collected through in-depth interviews and analyzed using the interactive model proposed by Matthew B. Miles and A. Michael Huberman, which includes data reduction, data display, and conclusion drawing. Findings: The findings indicate that honesty-based accounting—implemented through the principles of transparency, moral accountability, integrity, and ethical awareness—plays an important role in preventing fraud in BOS fund management. Integrity-based leadership acts as a tone at the top that reinforces ethical behavior among staff, while an organizational culture that discourages misconduct strengthens internal control practices. Furthermore, the study integrates Attribution Theory to explain how internal moral responsibility and ethical awareness influence honest behavior beyond procedural compliance. Ethics training in accounting practices was also found to support the development of internal accountability among financial administrators. Research Implications: This study contributes to the literature by integrating honesty-based accounting, local ethical values such as Lempu’ and Ada’ Tongeng, and Attribution Theory in the context of educational financial governance. Practically, the findings suggest that ethics training and value-based financial management programs should be strengthened to improve transparency and accountability in BOS fund management in vocational high schools.